Educational Values in the Local Wisdom of the Belief System of the Kregolan Seyegan Hamlet Community: A Study of the Prohibition on the Use of Gebyok Doors and the Construction of Regol Gates - Maria Sri Mulati; Muhammad Iqbal Birsyada (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study aims to explore the educational values embedded in local wisdom within the belief system of the community in Padukuhan Kregolan, Seyegan. Specifically, it examines the prohibitions against the use of gebyok doors and the construction of regol as part of the community’s traditional beliefs. This research employs a qualitative descriptive approach, with data collected through observation, in-depth interviews, and documentation. The findings reveal that these prohibitions are not merely cultural restrictions but contain symbolic meanings that reflect moral, social, and spiritual values. The educational values identified include respect for tradition, social harmony, obedience to norms, and environmental awareness. Furthermore, these values are relevant to character education and can be integrated into learning processes, particularly in contextual and culture-based education. Therefore, local wisdom in the belief system of the Kregolan community holds significant potential as a source of educational values that support the development of students' character and cultural awareness.